LINC00941 promotes glycolysis in pancreatic cancer by modulating the Hippo pathway - Ming Xu; Ran Cui; Lunhe Ye; Yongkun Wang; Xujing Wang; Qiqi Zhang; Kaijing Wang; Chunxiu Dong; Wenjun Le; Bo Chen (Elsevier, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of most lethal cancers and is projected to be the second leading cause of cancer deaths in the United States by 2030. The lack of effective treatment and increased incidence in PDAC encourage a deeper knowledge of PDAC progression. By analyzing a long noncoding RNA (lncRNA) dataset, we found that increased LINC00941 expression led to poor outcomes in PDAC patients. Furthermore, in vitro and in vivo experiments revealed that LINC00941 promoted PDAC cancer cell growth by enhancing aerobic glycolysis. Mechanistically, LINC00941 was found to interact with mammalian STE20-like protein kinase 1 (MST1), which facilitated the protein phosphatase 2A (PP2A)-mediated dephosphorylation of MST1, resulting in Hippo pathway activation and consequently, enhanced glycolysis in PDAC. These results suggest that LINC00941 plays a key role in regulating PDAC tumorigenesis, potentially highlighting novel avenues for PDAC therapy.